Serum antibody response to capsular polysaccharide, outer membrane, and lipooligosaccharide in children with invasive Haemophilus influenzae type b infections. - Claesson, B A (1987)
Serum antibodies against capsular polysaccharide (CPS), outer membrane (OM), and lipooligosaccharide (LOS) from Haemophilus influenzae type b were measured by enzyme-linked immunosorbent assay in acute- and convalescent-phase sera from 21 children between 3 months and 4 years of age with invasive H. influenzae type b infections. As expected, the levels of anti-CPS antibodies in the acute-phase serum samples were low or not detectable, as were the levels of antibodies against LOS. In contrast, all children had detectable antibodies against the OM in the acute-phase serum sample, indicating that they are of little or no importance for protection. An antibody response to CPS was noted in 13 of the 21 patients, mainly in the older children. An antibody response to the OM was seen in 16 patients, with no evident relation to age. The antibody response to the OM preparation, which consisted of proteins and LOS, was probably directed mainly against the OM proteins, since only six children showed a response, usually of low magnitude, of antibodies to LOS.